Koszty niewykorzystanych zasobów w rachunku kosztów działań - Wierzbiński, Marcin (Costs of Unused Capacity of Resources in Activity Based Costing (ABC), 2009)
In the article its author depicts different ways of treating costs of unused capacity of resources in activity based costing (ABC). The first way of treating theses costs was invented by R.S. Kaplan and R. Cooper who proposed calculating standard cost driver rates. To calculate theses rates we use budgeted rather than historical data and practical capacity rather than actual utilization of activities. In this model of ABC the costs of unused capacity of resources are allocated to activity costs. In the second model of ABC the costs of unused capacity are calculated at the level of resources and are not allocated to activity costs. The third model refers to the new concept of ABC called time driven activity based costing (TDABC) which was also invented by R.S. Kaplan. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 119-135